Keanekaragaman Jenis Burung pada Berbagai Tipe Habitat di Taman Nasional Kelimutu, Kabupaten Ende, Provinsi Nusa Tenggara Timur - Rischaardts Chornelis Manafe; Maria M. E. Purnama; Oki Hidayat; Fadlan Pramatana (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2024)
In the Kelimutu National Park area there is a tourist attraction, namely, Lake Kelimutu. The tourist attraction of Lake Kelimutu has a high beauty value, making it always crowded with tourists, both local and foreign. The presence of tourists can be a factor in the level of bird species diversity in the Kelimutu National Park area. This is because birds tend to be sensitive to human presence (Bötsch et al., 2017) so this study aims to determine the diversity of bird species in bird habitats around tourist objects. The method used in collecting data in the field is the path and point method. In data analysis, the method used is the Mackinnon's Species List method. The results of this study indicate that the presence of tourists does not affect the diversity of bird species in habitats around the Lake Kelimutu tourist area.